1996
DOI: 10.1016/s0009-9236(96)90169-1
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine methyltransferase activity in a Korean population sample of children*

Abstract: Thiopurine methyltransferase (TPMT) is a cytoplasmic enzyme that catalyzes the S-methylation of the cytotoxic drugs 6-mercaptopurine and azathioprine. Red blood cell (RBC) TPMT activity is subject to genetic polymorphism, and we have previously demonstrated an interethnic difference in TPMT activity. To investigate whether there was a race-related difference in RBC TPMT activity, TPMT was measured in a Korean population sample of 309 healthy children. Mean TPMT activity in healthy Korean children was 12.4 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 33 publications
4
19
0
1
Order By: Relevance
“…Nevertheless, the graphical representation of TPMT data clearly showed that distribution differed depending on disease. It has been suggested that the unimodal or normal distribution of TPMT activity is more characteristic of some Jewish [17], French [18], or East Asian populations [19]. On the contrary, in other European [20] and North American [21] populations a more evident trimodal distribution has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the graphical representation of TPMT data clearly showed that distribution differed depending on disease. It has been suggested that the unimodal or normal distribution of TPMT activity is more characteristic of some Jewish [17], French [18], or East Asian populations [19]. On the contrary, in other European [20] and North American [21] populations a more evident trimodal distribution has been described.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that differences in assay conditions can cause significant differences in TPMT activity measured in different laboratories [5]. We used a simple HPLC method to determine TPMP activity and produced results that seemed to be comparable to that of white populations (about 13 U ml -1 RBC) [3,4] and Korean children (12.4 U ml -1 RBC) measured by the standard radiochemical assay [23]. The 5.3-fold range in TPMT activity among Chinese Children in this study is similar to the 4.0-fold range observed in Korean Children [23].…”
Section: Discussionmentioning
confidence: 99%
“…We used a simple HPLC method to determine TPMP activity and produced results that seemed to be comparable to that of white populations (about 13 U ml -1 RBC) [3,4] and Korean children (12.4 U ml -1 RBC) measured by the standard radiochemical assay [23]. The 5.3-fold range in TPMT activity among Chinese Children in this study is similar to the 4.0-fold range observed in Korean Children [23]. In addition, this study observed minor and nonsignificantly higher TPMT activity in girls than boys.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature showed that Caucasians have higher median TPMT activity in erythrocytes than black populations [10,11,21], but North American Caucasians, European Caucasians, and Asian populations (healthy Korean children) [11,21,22] have approximately the same median TPMT activity in erythrocytes. The frequency of TPMT genetic variation in Thai children in the present study is the same as that reported in the Caucasian populations, therefore TPMT genotype in Thai children could reflect TPMT phenotypic activity in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%